Correlation between the Number of Leucocytes and Neutrophil to Lymphocytes Count Ratio in Children with Pneumonia at RSUD Koja Jakarta - Arlita Dian Yuniamawati; Sulasmi (Institute of Computer Science (IOCS), 2022)
Pneumonia is an acute lower respiratory tract infection that affects the lungs. This disease is one of infant and toddlers' biggest causes of death. Immature immunity, poor air quality, poor sanitation and nutrition, and incomplete immunization make children vulnerable to this disease. This study used an analytic observational method with a cross-sectional research design. The research subjects used as many as 30 respondents with pneumonia in children with an age range of 1 year -17 years who were in the pediatric ward at Koja Hospital. The study was conducted at the Koja Hospital laboratory from February to June 2022. The sample in this study was the result of a complete blood count, namely the examination of the leukocyte count and the value of the neutrophil-lymphocyte ratio in pediatric patients with pneumonia. The data was collected by performing a complete blood count using the Sysmex XN 1000 Hematology Analyzer. Data analysis in this study used the Pearson product-moment correlation test with a 95% confidence level. Using the Statistical product and service solution version 23 program. The results showed a significance value (p) of 0.05 > 0.03. This study concludes that there is a correlation between the number of leukocytes and the value of the neutrophil-lymphocyte ratio in pediatric patients with pneumonia at Koja Hospital, Jakarta.